Efektivitas Implementasi Pembelajaran Model Problem Based Learning (PBL) Diintegrasikan dengan predict – observe – explain (POE) terhadap Prestasi Belajar Siswa Ditinjau dari Kreativitas dan Kemampuan Inferensi Siswa - WAHYUNI, DWI; SUDARISMAN, SUCIATI; Sugiyarto, Sugiyarto (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
The purpose of this research is to know the influence of PBL model, POE model and integrated PBL-POE towards students’ achievement, overviewed from students’creativities and students’ inference abilities.This research achievement used students’ creativities and students’ inference abilities method with factorial design 3x2x2. The research population is grade XI science class student SMA Negeri 1 Bojonegoro. Sample research is decided randomly with cluster random sampling technics. In 2013/ 2014 academic year, it consisted of three classes. Experiment class I was given PBL model treatment consist of 32 students, experiment class II was given POE model treatment consists of 32 students and experiment class III was given integrated PBL-POE treatment and consists of 32 students. Data accumulation used technic test for cognitive study result, questionnaire for affective study result, psycomotor, creativity and inferency ability. Hyphothesis research test uses anova which three ways cell is not equel with help of software SPSS 18. The research result: 1) There is influence from integrated PBL-POE towards students’ achievement in cognitive, affective, psychomotor; 2) There is creativity influence towards students’ achievement; 3) There is no influence for students’ inferency abilities towards students’ achievement; 4) There is no learning model interaction with creativity low and high category influence towards students’ achievement; 5) There is learning model interaction with students’ inference abilities low and high category influence towards students’ achievement; 6) There is influence from interaction between creativity and students’ inferency abilities toward students’ achievement; 7) There is no influence from interaction between PBL model with students’ creativity and students’ inference abilities towards students’ achievement